2013
DOI: 10.1128/jcm.03432-12
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Digital Fluorescence Microscopy for Diagnosis of Tuberculosis

Abstract: Access to sputum smear microscopy in high-tuberculosis (TB)-burden regions is limited by a scarcity of microscopes and experienced technicians. We evaluated the accuracy of CellScope, a novel digital fluorescence microscope that may expand access to microscopy. The study utilized smear microscopy slides prepared from sputum specimens submitted by consecutive adults with >2 weeks of cough who were admitted to Mulago Hospital (Kampala, Uganda). Conventional light-emitting diode (LED) fluorescence microscopy (FM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 26 publications
(25 reference statements)
0
33
0
1
Order By: Relevance
“…Recently, several low-cost, portable and innovative microscopes have been introduced in the literature [4246]. Their focus is largely on field-diagnosis imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several low-cost, portable and innovative microscopes have been introduced in the literature [4246]. Their focus is largely on field-diagnosis imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Although NAATs are widely used in Europe [33,59], their high cost and level of technical support hindered the widespread adoption in TB endemic countries. Improving diagnosis in high-income countries is a strategic goal in TB research, and the pipeline of diagnostic tools is rapidly growing: new ways of performing sputum smear microscopy and innovative technologies for molecular diagnosis have already been endorsed by WHO, or are under investigation [60]. To respond to the urgent need for simple and rapid diagnostic tools at the point of treatment in high-burden countries, a fully automated molecular test for M. tuberculosis detection and resistance to RIF testing was developed (Xpert®MTB/ RIF) and has been endorsed by WHO in December 2010 [56].…”
Section: Advanced Diagnostic Techniquesmentioning
confidence: 99%
“…Tapley and colleagues developed a prototype system that acts similarly to a cellular phone's camera and display screen to capture and display a fluorescent microscopy live feed. (28) They demonstrated that minimally qualified individuals could effectively use the system to interpret sputa for the presence of mycobacteria, and the authors suggest that this method could be enhanced by transmitting some of the images to remote experts. In 2009, Zimic and coauthors described the use of cellular telephones to transmit images of mycobacteria grown in a drug susceptibility test system.…”
Section: Clinical Microbiology Applicationsmentioning
confidence: 99%